2004
DOI: 10.1161/01.str.0000137412.35700.0e
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Model of Microembolic Stroke and Reperfusion

Abstract: Background and Purpose-To test the role of fibrinolysis in stroke, we used a mouse model in which preformed 2.5-to 3-m-diameter fibrin microemboli are injected into the cerebral circulation. The microemboli lodge in the downstream precapillary vasculature and are susceptible to fibrinolysis. Methods-We injected various doses of microemboli into the internal carotid artery in mice and characterized their distribution, effects on cerebral blood flow, neurological deficit, infarct area, and spontaneous dissolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
54
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 19 publications
1
54
0
Order By: Relevance
“…22 In a photochemical vascular injury model, the outcome of tPA-deficient mice depended on the severity of injury. 16 Finally, in a mouse model of microembolic stroke, 14 tPA-deficient animals displayed a delayed dissolution of the cerebral emboli and an aggravated ischemic infarct. It is possible that differences in clot structure, dependent on the model used, may determine outcome of rtPA treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 In a photochemical vascular injury model, the outcome of tPA-deficient mice depended on the severity of injury. 16 Finally, in a mouse model of microembolic stroke, 14 tPA-deficient animals displayed a delayed dissolution of the cerebral emboli and an aggravated ischemic infarct. It is possible that differences in clot structure, dependent on the model used, may determine outcome of rtPA treatment.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Other workers have used a second type of model involving injection of autologous or heterologous preformed fibrin, blood clots, 11,12,13 including microemboli, 14 or in situ clot formation by using rose Bengal. 15,16 Although these last models are closer to what happens in patients with stroke, they lack reproducibility and uniformity in the resulting infarct volume, the location of the lesion, 17,18 and/or display a high degree of mortality 19 rendering the statistical analysis of the data confusing (for review, 20 ).…”
mentioning
confidence: 99%
“…Immediately after intravascular injection, the fibrin microemboli form aggregates invested with blood elements, which lodge in the downstream vasculature . Previous studies showed that within 5 min after injection, the chosen dose of emboli (ϳ1.4 ϫ 10 6 particles) causes ϳ80% cessation of blood flow in the MCA, leading to an extensive ipsilateral cerebral infarction, similar to that caused by 20 h of mechanical MCA occlusion in the standard filament model (Atochin et al, 2004).…”
Section: Methodsmentioning
confidence: 97%
“…We studied the effect of scFv-uPA in a mouse model of cerebrovascular thrombosis induced by injecting 125 I-labeled fibrin emboli (ϳ3 m in diameter, prepared as described previously; Atochin et al, 2004;Ding et al, 2005), into the middle cerebral artery (MCA). Immediately after intravascular injection, the fibrin microemboli form aggregates invested with blood elements, which lodge in the downstream vasculature .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation